2007
DOI: 10.7863/jum.2007.26.11.1587
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of the Intraductal Component of Invasive Breast Cancer

Abstract: Combined assessment with mammography and sonography offers more accurate information for the presence of an intraductal component and the extent of a tumor than each separate assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Breast microcalcifications are considered an important finding for the diagnosis of breast cancer, making their correct visualization and analysis crucial for early detection. [5][6][7][8][9][11][12][13][24][25][26][27][28][29][30][31] Mammography is considered the only reliable method to identify and classify microcalcifications. [1][2][3][4][5][6][7][8][9][10][11][12] Current US technology is not considered a reliable method for the detection or evaluation of microcalcifications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Breast microcalcifications are considered an important finding for the diagnosis of breast cancer, making their correct visualization and analysis crucial for early detection. [5][6][7][8][9][11][12][13][24][25][26][27][28][29][30][31] Mammography is considered the only reliable method to identify and classify microcalcifications. [1][2][3][4][5][6][7][8][9][10][11][12] Current US technology is not considered a reliable method for the detection or evaluation of microcalcifications.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evaluation of breast microcalcifications by gray scale ultrasound imaging (US) is not usually performed, due to the limitations of this imaging technique in identifying microcalcifications. There have been some attempts by researchers to use gray scale US to identify microcalcifications, but even the most promising results from these studies/methods do not support the clinical use of gray scale US for the evaluation of microcalcifications 4 , 5 , 7 9 , 11 13 , 15 , 26 29 , 32 , 33 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been widely reported that ultrasonography is more sensitive than mammography in breast cancer diagnosis (Kang et al, 2007;Huang et al, 2012;Lehman et al, 2012;Ya-Jie et al, 2012). Although the specificity of mammography is higher than that of ultrasonography (Birdwell, 2009), in the view of breast cancer screening, the higher sensitivity is more beneficial for early diagnosis of breast cancer.…”
Section: Introductionmentioning
confidence: 99%